ANALISIS KESALAHAN BERBAHASA CAMPUR KODE DALAM MENULIS TEKS LAPORAN PERCOBAAN PADA SISWA SMP - Inayati Anggraeni Juanda; Yupu Medaldipa; Mekar Ismayani (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2019)
This research was motivated because of the errors found in the field. The problem that was found was that there was a code mix by class IX F SMP students when writing the text of the experimental report. Code mixing occurs because of the fragments of other languages namely Sundanese (B1) into the writing that is being studied, namely Indonesian (B2). This study aims to determine how much influence the student's code interferes in writing the text of the experimental results report and how to overcome these errors. The method used is a qualitative research method, this method is a method that produces data in the form of words or sentences both oral and written. Based on the results of the study, from 1-5 groups of students consisting of 5 people in the results of the writing, there are several vocabulary words that use Sundanese (B1), namely the words peso, onion bodas, coet, sweet potato kulub, pecin, katel, uyah, parud, and implant. If present, the result is 36%, so it can be concluded that in the student writing results there is a language error that is code mixing.